Я - вор в законе. Медвежатник - Сухов Евгений Евгеньевич (Я - вор в законе, 2002)
Экземпляры: ф-4 (20180912) / Инвентарный номер: 52507 / Цена: 50.00 / Сис.шифр: Р2 / Авт.знак: С91 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6